Determinants of investment activity of Russian companies in the real sector under financial constraints. - E. V. Khudko; E. V. Dondopova (Вестник университета)
The level of accessibility to various sources of financing plays a crucial rolein formation of an investment strategy.   The purpose of the article is to identify and analyse factors influencing the volume of investment expenditures of public Russian enterprises in the real economic sector with consideration to the degree of financial constraints.   The research is based on division of companies into more and less financially constrained. The following characteristics were chosen as criteria for segmentation: size, age of the business and placement of corporate bonds on the exchange. A regression analysis specified similarities and differences among determinants of investment activity of more and less financially constrained companies. The key common factor that has an impact on this characteristic of organisations in both groups is investment expenditures of the previous period. Investments of more financially constrained companies have shown a strong dependence on indicators of current cash flow and capital structure. At the same time, the volume of expenses of less financially constrained companies is more influenced by the indicator of accumulated tangible assets. The results of the research may interest enterprises in the real sector when assessing the degree of their financial constraint and determining the volume of investment expenditures.